Pediatric cancer pathology review from a single institution: Neuropathology expert opinion is essential for accurate diagnosis of pediatric brain tumors. Issue 1 (4th July 2017) - Merabi, Zeina; Boulos, Fouad; Santiago, Teresa; Jenkins, Jesse; Abboud, Miguel; Muwakkit, Samar; Tarek, Nidale; Zaatari, Ghazi; Jeha, Sima; El‐Solh, Hassan; Saab, Raya
Abstract: Background and objectives: Second pathology review has been reported to improve accuracy in oncologic diagnoses, including pediatric malignancies. We assessed the impact of second review on the diagnosis of pediatric malignancies at a tertiary care referral center in Beirut, Lebanon. Methods: Pathology reports of patients treated at the Children's Cancer Institute in Lebanon were retrospectively reviewed for the period 2008–2016 and compared with same samples' diagnoses at St. Jude Children's Research Hospital. Diagnostic disagreements were divided into major, minor, and none based on their effect on diagnosis and/or patient management. Results: Second review was requested for 171 cases, accounting for 19% of all cases during that period. Second opinion was mostly requested for brain tumors (62% of all brain tumor cases) and neuroblastoma for NMYC testing (65% of all neuroblastoma), while hematologic malignancies had the fewest referrals (3% of all hematologic cases). Major disagreements in second review occurred in 20 cases (12% of total), and minor disagreements in 21 cases (12% of total). The largest proportion of major disagreements (71%) occurred in pediatric brain tumors, and novel molecular tests contributed to the diagnosis in 55% of these cases. Conclusions: The availability of a specialized pediatric neuropathologist and a basic panel of relevant molecular testing are essential for appropriate diagnosis of pediatric brain tumors. Centers that do not have the available infrastructure in place can benefit greatly from second review referrals for this challenging subset of tumors.